Development of a miniature time-of-flight mass spectrometer coupled with an improved substrate-enhanced laser-induced acoustic desorption source (SE-LIAD/TOF-MS). Issue 13 (15th June 2021) - Yu, Jingxiong; Chen, Yuwan; Zhang, Jiangle; Chen, Shanjun; Wang, Qiaolin; Qin, Zhengbo; Tang, Zichao
Abstract : In contrast to the normal LIAD method, the enhanced signals were obtained using substrate-enhanced LIAD source (SE-LIAD) being about 5-fold to 14-fold enhancement. Abstract : A novel, compact and sensitive SE-LIAD/TOF-MS has been described. It facilitates fast sample preparation, and a full mass spectrum is acquired efficiently and sensitively. More importantly, it features the detection of non-acidic and non-basic or non-polar species, which is not suitable for determination by ESI and MALDI techniques. In this technique, standard samples, carbazole and melamine, are prepared on a Ti foil with a quartz plate attached to the backside of the Ti foil to perform a laser-induced acoustic desorption experiment (SE-LIAD) coupled to TOF-MS for analysis. Enhanced signals are observed with about 5.6 to 13.8 times higher than that obtained in the standard LIAD method, dependent on different ionization techniques. Compared to the EI spectra, the PI spectra for both species show intact and sharp molecular peaks. The limits of detection (LOD) of melamine were evaluated experimentally in the range from ∼2–6 pg (EI/MS mode) to ∼0.3–0.5 ng (VUV-SPI/MS mode). Thus, the method in this study exhibits rapid qualitative and quantitative analysis with good sensitivity, being free of the complex matrix influences.